2015
DOI: 10.1155/2015/678527
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Strongly Affects Mitochondrial Ribosomal Proteins and Translocases, as Shown by Quantitative Proteomics of HeLa Cells

Abstract: Hypoxia is an important and common characteristic of many human tumors. It is a challenge clinically due to the correlation with poor prognosis and resistance to radiation and chemotherapy. Understanding the biochemical response to hypoxia would facilitate the development of novel therapeutics for cancer treatment. Here, we investigate alterations in gene expression in response to hypoxia by quantitative proteome analysis using stable isotope labeling with amino acids in cell culture (SILAC) in conjunction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 49 publications
5
35
0
Order By: Relevance
“…However, we did not observe an increased expression of NeuGc GM3 using media supplemented with fetal bovine serum, which contains NeuGc ( Figure S2). Sialin (SLC17A5) was not identified in our recent SILAC study, not even at below-significance levels, even though 26 other proteins from the SCL-family were detected, of which four were upregulated [34]. One of them was the GM3 synthase (ST3GAL5/SLC35E1) responsible for catalyzing the covalent addition of sialic acid to lactosylceramide to generate the GM3 ganglioside.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…However, we did not observe an increased expression of NeuGc GM3 using media supplemented with fetal bovine serum, which contains NeuGc ( Figure S2). Sialin (SLC17A5) was not identified in our recent SILAC study, not even at below-significance levels, even though 26 other proteins from the SCL-family were detected, of which four were upregulated [34]. One of them was the GM3 synthase (ST3GAL5/SLC35E1) responsible for catalyzing the covalent addition of sialic acid to lactosylceramide to generate the GM3 ganglioside.…”
Section: Resultsmentioning
confidence: 68%
“…In the same study, we found an iron-sulfur [Fe 2 S 2 ]-containing protein to be significantly up-regulated under hypoxic conditions (1.9 fold; p=0.0057), while many other mitochondrial proteins were down-regulated [34]. The protein in question is subunit B of the succinate dehydrogenase complex (which represents complex II of the respiratory chain).…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…Additional genes were significantly associated in population-specific analyses, including the components of the oxidative phosphorylation system, and a majority of the small subunit proteins have been implicated in disease [ 88 ]. The expression of several small and large subunit proteins are altered in a hypoxic environment [ 89 ]. MRPS33 expression varies with oxygen treatment in COPD [ 90 ].…”
Section: Gene-based Results Smentioning
confidence: 99%